2020
DOI: 10.1115/1.4049353
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bands in Materials Processing: Understanding the Mechanics of Flow Localization From Zener's Time to the Present

Abstract: Shear banding is a material instability in large strain plastic deformation of solids, where otherwise homogeneous flow becomes localized in narrow micrometer-scale bands. Shear bands have broad implications for materials processing and failure under dynamic loading in a wide variety of material systems ranging from metals to rocks. This year marks 75 years since the publication of Zener and Hollomon's pioneering work on shear bands (Zener and Hollomon, J Appl. Phys., 15, 22–32, 1944), which is widely credited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 124 publications
(219 reference statements)
0
5
0
Order By: Relevance
“…In terms of energy, in homogeneous processes such as shear bands and crazing would absorb energy (Donald & Kramer, 1982). This knowledge enhances the design of new materials and increases the endurance of existing materials to extreme working conditions, which is the focus of recent research activities (Tang et al, 2018;Viswanathan, Yadav, & Sagapuram, 2020;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of energy, in homogeneous processes such as shear bands and crazing would absorb energy (Donald & Kramer, 1982). This knowledge enhances the design of new materials and increases the endurance of existing materials to extreme working conditions, which is the focus of recent research activities (Tang et al, 2018;Viswanathan, Yadav, & Sagapuram, 2020;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A potential complication is that certain multi-phase engineering alloys (e.g. high-strength steels, Ti and Ni alloys) are prone to shear localization, especially at high V0 [10,11,49]. While this is not a fundamental limitation, in that the proposed parameter estimation method is independent of the nature of the flow, this will, however require the use of special imaging techniques with even better spatial/temporal resolution to accurately capture the localized flow; some of our preliminary work [26,27] touches upon full-field measurement issues in the presence of shear localization.…”
Section: Discussionmentioning
confidence: 99%
“…In these applications, the material deformation is well into the plastic regime and often characterized by extreme strains of several hundreds to thousand percent, strain rates in the range of 10 to 106/s, and significant plastic heating. Other examples which involve large plastic deformation and flow, albeit over small localized volumes, include tribological contacts [4], erosion [5], indentation [6,7] and deformation fields in the vicinity of a fast-running ductile crack or a shear band [811]. For computational finite-element models to provide accurate predictions of the material behaviour and flow kinematics, it is imperative that the parameters of the material’s constitutive law ‘the law that relates the flow stress to plastic strain, strain history, strain rate and temperature’ be calibrated under relevant large deformation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor room-temperature ductility of MGs under tensile loading is a big challenge to apply them in engineering structures 4,5 . Several works have been done to identify mechanism of flow stress behavior of MGs under tensile loading and few studies have succeeded to improve tensile flow characteristics in amorphous alloys [6][7][8] . Tensile loading sensitivity is so high that even the MG composites are exposed to the brittle fracture 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In another work, a failure mechanism based constitutive model for bulk metallic glass was proposed, in which the nucleation and coalescence of nano-voids during the deformation was estimated 21 . Another study presented a thermodynamically constitutive model of MGs by extending an infinitesimal deformation approach, in which the multiplicative decomposition of deformation gradient and additive decomposition of free energy was considered 22 . Yao et al 23 developed a size-dependent constitutive model of MGs and found that the size effect is a crucial factor in micro forming processes.…”
Section: Introductionmentioning
confidence: 99%